2016
DOI: 10.1002/jaba.354
|View full text |Cite
|
Sign up to set email alerts
|

Can pictures promote the acquisition of sight‐word reading? An evaluation of two potential instructional strategies

Abstract: Sight-word instruction can be a useful supplement to phonics-based methods under some circumstances. Nonetheless, few studies have evaluated the conditions under which pictures may be used successfully to teach sight-word reading. In this study, we extended prior research by examining two potential strategies for reducing the effects of overshadowing when using picture prompts. Five children with developmental disabilities and two typically developing children participated. In the first experiment, the therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…We selected these onsets because they have appeared in previous studies. For example, Olenick and Pear () used an immediate onset arrangement, Richardson et al () used an early onset arrangement, and Carroll et al () used a late onset arrangement. It may be relevant to note that the immediate onset differs from the other onset conditions in that the transition to differential reinforcement is not made as a function of the level of unprompted correct responses emitted by the participant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected these onsets because they have appeared in previous studies. For example, Olenick and Pear () used an immediate onset arrangement, Richardson et al () used an early onset arrangement, and Carroll et al () used a late onset arrangement. It may be relevant to note that the immediate onset differs from the other onset conditions in that the transition to differential reinforcement is not made as a function of the level of unprompted correct responses emitted by the participant.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the experimenter delivered the edible amount plus praise following unprompted correct responses and a lower quality, smaller magnitude, or leaner schedule of reinforcement was provided for prompted correct responses. A 33% criterion was selected to closely resemble the Richardson et al () criterion; however, a change from nondifferential reinforcement to differential reinforcement was not made until two consecutive sessions to more closely resemble the criterion for the late onset condition in the present study. Differential reinforcement late onset . The experimenter delivered the edible amount plus praise for all unprompted and prompted correct responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimenters elected to arrange the training conditions and stimulus set sizes to match procedures in previous studies. For example, previous investigations provided repeated presentations of a stimulus within sessions when conducting training with smaller stimulus set sizes (e.g., Carroll, Owsiany, & Cheatham, ; Marchese et al, ; McGhan & Lerman, ; Richardson et al, ). Nevertheless, it is possible that conducting sessions in which participants receive one exposure per stimulus (e.g., a session composed of three trials with three stimuli presented one time each) could produce different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the same researchers concluded that the sight words teaching could be the first step to a complete educational program of reading for students with ID. Finally, according to Richardson et al (2017) another possible strategy which could ensure that the student pays attention in both the image and the word is the matching of words and images which can benefit the acquirement of key-word reading.…”
Section: Reading Interventions For Students With Idmentioning
confidence: 99%